Handling of Missing Persons Reports Suspected of Victims of Crimes and Problems in Uncovering the Truth of the Case by the Salaman Sector Police - Nugrahanto, Oka Putra; Basri, Basri; Kurniaty, Yulia (West Science Law and Human Rights, 2025)
The development of society and globalization have made crimes such as kidnapping, murder, and rape more diverse. In Indonesia, missing persons reports are often the beginning of the revelation of criminal acts, but the handling by the police is still slow and not uniform. Some reports are only processed after 1x24 hours, even though time is crucial. At the Salaman Police Station, 32 cases of missing persons in 2021-2025 led to criminal acts, showing the need for improvement. Handling must be fast, precise, and uniform without administrative delay, in accordance with the provisions of the Criminal Procedure Code and police regulations that require immediate service and victim protection. Standard regulations are needed that regulate the operational standards for handling missing persons reports, especially if they contain suspected criminal acts. This research uses a normative juridical method with a legal approach and a conceptual approach. To strengthen the argument, an interview was conducted with the Head of the Criminal Investigation Unit of the Salaman Police in a structured manner. This research uses a normative-empirical type of research. The approaches used in this study are the laws and regulations approach, and the case approach. Normative-empirical research uses primary data and is supported by secondary data. The results of the study concluded that the action taken by the Salaman Sector Police of Magelang Regency when there is a report of a missing person suspected of being a victim of a crime is to follow up in accordance with the SOP for the Acceptance of Police Reports and the SOP for Public Visits in accordance with Article 7 letters c and d of the Regulation of the National Police of the Republic of Indonesia Number 7 of 2022 concerning the Professional Code of Ethics and the Commission of the Code of Ethics of the National Police of the Republic of Indonesia,  and Article 1 number 4 of the Regulation of the Chief of the National Police of the Republic of Indonesia Number 6 of 2019 concerning Criminal Investigation. The Salaman Police directly followed up on missing person complaints without following the 1 x 24-hour waiting mechanism, and followed up on missing person complaints in the same way by following up on reports of suspected criminal acts. The reason is that missing person complaints can develop into reports of alleged criminal acts, as well as problems in uncovering the truth of the case of handling missing persons reports in the Salaman Sector Police, Magelang Regency is based on the theory of factors that affect law enforcement by Soerjono Soekanto, namely regarding community factors and cultural factors.